2011
DOI: 10.2351/1.3622205
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity measurement of silver nanofluid by thermal lens technique

Abstract: The thermal lens technique was utilized in silver nanofluid containing silver nanoparticles in polyvinylpyrrolidone solution to study the effect of nanoparticle size on thermal diffusivity. The different sizes of silver nanoparticles were prepared by irradiating the solution of silver nitrate in polyvinylpyrrolidone with respective dose of γ-radiation. The average sizes of particle in the prepared samples were measured using nanophox machine. The thermal lens measurement was carried out by using a diode laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…So far the ability of this technique for measurement on the thermal diffusivity of nano-fluids was confirmed by many researchers [18]- [21]. In this work, we used pulsed laser TL technique to measure the thermal diffusivity of fluids containing Cu-NPs which were prepared by γ-irradiation method.…”
Section: Introductionmentioning
confidence: 92%
“…So far the ability of this technique for measurement on the thermal diffusivity of nano-fluids was confirmed by many researchers [18]- [21]. In this work, we used pulsed laser TL technique to measure the thermal diffusivity of fluids containing Cu-NPs which were prepared by γ-irradiation method.…”
Section: Introductionmentioning
confidence: 92%
“…The details of the absorption band depend on the size and shape of the nanoparticle as well as the aggregation state: the bigger the nanoparticle or the aggregate, the bigger the redshift [18]. Previous works that have reported the thermal diffusivity of AgNF employing the thermal lens technique considered silver nanoparticles (AgNPs) produced by radiation [19,20] and laser ablation [21]. Besides the thermal lens approach, others techniques such as microflash [22] and the photopyroelectric technique [23] have been employed to determine in AgNFs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that nanofluids exhibit higher thermal conductivity and thermal diffusivity than base fluids themselves. Thermal research in nanofluids has been mainly focused in thermal conductivity measurements [3-5], but in recent years, other techniques have been developed for thermal diffusivity measurements in nanofluids, such as the hot-wire technique and the thermal lens spectrometry [6-8]. However, these methodologies are limited due to the difficulty in achieving accurate results, the complexities in their theoretical model and the amount of sample required for measurements.…”
Section: Introductionmentioning
confidence: 99%